Combined Shear-Tension Loading of Composite Dowels in Cracked Concrete—Experimental Investigations and Design - Georgios Christou; Kevin Wolters; Jan Ungermann; Martin Classen; Josef Hegger (Applied Sciences, 2022)
The importance of slim decks has led engineers to the exploration of high-strength materials and also of innovative shallow shear connectors, such as composite dowels in the case of composite constructions. Minimizing the overall slab depth often leads to composite girders being weakened by means of web openings that are necessary for installations such as ventilation ducts. Depending on the geometrical and loading conditions, some of the shear connectors are subjected to a combination of tensile and shear forces. However, the load-bearing behaviour of these connectors has only been rudimentarily investigated in the case of shear-tensile interaction. In addition, the load-bearing capacity of composite dowels under combined tensile and shear forces has not been investigated in cracked concrete. Earlier investigations under pure shear and pure tensile loading indicate a dependence of the connectors’ load-bearing behaviour on the crack width, so that under combined loading, a similar influence is expected. In this paper, experimental investigations on composite dowels in transversely cracked concrete under systematically varied shear-tension loading combinations are presented. Hereby, predefined crack widths and patterns were considered using a special test rig. Finally, a design approach for concrete failure of composite dowels under shear-tension loading is proposed based on the test results.